2011
DOI: 10.1371/journal.pone.0027769
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Bispectral Index-Guided Propofol Infusion for Flexible Bronchoscopy Sedation: A Randomized Controlled Trial

Abstract: ObjectivesThere are safety issues associated with propofol use for flexible bronchoscopy (FB). The bispectral index (BIS) correlates well with the level of consciousness. The aim of this study was to show that BIS-guided propofol infusion is safe and may provide better sedation, benefiting the patients and bronchoscopists.MethodsAfter administering alfentanil bolus, 500 patients were randomized to either propofol infusion titrated to a BIS level of 65-75 (study group) or incremental midazolam bolus based on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 32 publications
3
89
2
1
Order By: Relevance
“…9 It has been widely applied during general anesthesia and procedures requiring consciousness sedation to avoid oversedation, reduce adverse effects, and prevent awareness during anesthesia. 10,11 Loss of consciousness has been reported to occur at BIS values between 60 and 80. 12,13 Lately, several DISE studies have also investigated BIS during propofol sedation to evaluate sedation levels.…”
Section: Bispectral Index In Evaluating Effects Of Sedation Depth On mentioning
confidence: 99%
“…9 It has been widely applied during general anesthesia and procedures requiring consciousness sedation to avoid oversedation, reduce adverse effects, and prevent awareness during anesthesia. 10,11 Loss of consciousness has been reported to occur at BIS values between 60 and 80. 12,13 Lately, several DISE studies have also investigated BIS during propofol sedation to evaluate sedation levels.…”
Section: Bispectral Index In Evaluating Effects Of Sedation Depth On mentioning
confidence: 99%
“…For moderate sedation a depth of sedation should not be greater than that of level 3. Bispectral (BIS) index monitoring is an electroencephalographic-based method of assessing a patient's level of consciousness and has been used in two trials of moderate sedation for bronchoscopy [20,21]. Both studies concluded that BIS can be used safely by the nonanaesthetist to titrate sedation with propofol.…”
Section: Safe Delivery Of Moderate Sedationmentioning
confidence: 99%
“…These studies have demonstrated that sedation with propofol compared to no sedation leads to less cough, pain, sensation of asphyxiation, total amnesia and improved tolerance of the procedure with no differences in oxygen saturations between the groups [5]. Compared to sedation with midazolam, propofol has similar efficacy and safety [21] but faster onset of action and a more rapid patient recovery for propofol leading to early discharge [20,21,[54][55][56] and improved patient tolerance [20,21,[54][55][56]. Propofol can be administered with other pharmacological agents including opiates.…”
Section: Propofolmentioning
confidence: 99%
“…Bu konuda yapılan çalışmalarda propofol uygulamasının amnezi yaparak, öksürük ve boğulma hissini azaltarak işlem toleransını artırdığı gösterilmiştir (2). Midazolamla karşılaştırıldığında, propofol benzer etkinlik ve güvenirliliğe sahiptir ancak etkisinin hızlı başlaması ve anesteziden hızlı çıkış hem de hasta toleransının daha iyi olması nedeniyle giderek daha fazla önerilmeye başlanmıştır (14,19). Propofol, analjezi sağlamak, öksürüğü azaltmak, gerekli propofol dozunu azaltmak ve anestezi ve sedasyonu artırmak için opiyat ve sedatiflerle kombinasyon tedavisinde de kullanılabilir (20,21).…”
Section: Propofolunclassified